The Effect of Diaphragmatic Breathing on Reducing Stress Levels in Nurses - Dhawo, Maria Silvana; Sadu, Bernadus; Wicaksono, Utomo (Babali Nursing Research, 2024)
Introduction: Stress is a common psychological problem faced by nurses in Indonesia during the pandemic, especially ER and ICU. This study aims to analyse the effect of diaphragmatic breathing exercises on reducing stress levels in nurses by using the NaDa Android Application. Methods: This study employed a quasi-experimental pre-test and post-test with a control group design. A total of 33 nurses in the Emergency room (17) and the Intensive Care Unit (16) were recruited by using purposive sampling. The control group was given health education and diaphragmatic breathing while the intervention group practiced diaphragmatic breathing using the NaDa Android application for 12 weeks. The data were collected by Perceived Stress Scale-10 and then analysed using a t-test. Result: The average stress level among nurses in the intervention group was 17.53 which reduced to 12,94. The average stress level among nurses in the control group was 21.06 which reduced to 19.88. There was no significant effect on the control group who practiced diaphragmatic breathing (p=0.061). In contrast with the intervention group who have a significant effect regarding stress reduction (p=0.000). The diaphragmatic breathing exercises by Nada Application had an effect on decreasing the stress levels among nurses compared to the respondents in the control group (p=0.000). Conclusion: Diaphragmatic breathing exercises can be recommended to nurses to help them cope with psychological stress and to provide relaxation responses. It also can be an alternative prevention of psychological disorders such as high stress, reducing the use of pharmacological therapy in preventing stress and anxiety.